Advances in intelligent data analysis XI : 11th International Symposium, IDA 2012, Helsinki, Finland, October 25-27, 2012. Proceedings - Klawonn, Frank; Tucker, Allan; Hollmén, Jaakko (Lecture Notes in Computer Science, 2012)
This book constitutes the refereed proceedings of the 11th International Conference on Intelligent Data Analysis, IDA 2012, held in Helsinki, Finland, in October 2012. The 32 revised full papers presented together with 3 invited papers were carefully reviewed and selected from 88 submissions. All current aspects of intelligent data analysis are addressed, including intelligent support for modeling and analyzing data from complex, dynamical systems. The papers focus on novel applications of IDA techniques to, e.g., networked digital information systems; novel modes of data acquisition and the associated issues; robustness and scalability issues of intelligent data analysis techniques; and visualization and dissemination results.